ANXIETY OF ADOLESCENT VICTIMS OF SEXUAL HARASSMENT - Mahendra, Muhammad Aldy; Hariko, Rezki (Universitas Negeri Padang, 2023)
Sexual harassment happens a lot to teenagers in today's society. The emergence of opportunities for sexual harassment is because some people, both men and women, do not gain sufficient knowledge so that they think that speech, movements, or actions that have sexual connotations are not reprehensible, but are commonplace as a way to increase intimacy between individuals. This study aims to analyze the anxiety experienced by adolescent victims of sexual harassment. This type of research is qualitative research in the form of a case study. Data collection in this research is interview guidelines, observation, and documentation. The results of this study explain that the victim experienced anxiety after the incident, but after time passed the victim could overcome the anxiety he experienced.